2017
DOI: 10.1021/acsbiomaterials.7b00110
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Graphitic-C3N4 Quantum Dots for Microwave-Induced Photodynamic Therapy

Abstract: Here, we report our new observations on graphitic-phase carbon nitride (g-C3N4) quantum dots (QDs) as agents for microwave induced photodynamic therapy (MIPDT). For the first time, we observed that singlet oxygen is produced in g-C3N4 QDs by microwave irradiation, which can be used for tumor destruction. The results of live/dead staining and flow cytometry show that g-C3N4 QDs based MIPDT can effectively kill cancer cells and promote tumor cell death. In addition, the cell viability and hemolysis tests in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Their average diameter is 4.1 nm as measured from 100 individual particles (Figure c). Figure b shows a representative image of an individual nanoparticle, indicating high crystallinity with a lattice parameter of 0.33 nm, a value that is in good agreement with the 002 plane of g‐C 3 N 4 ,…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Their average diameter is 4.1 nm as measured from 100 individual particles (Figure c). Figure b shows a representative image of an individual nanoparticle, indicating high crystallinity with a lattice parameter of 0.33 nm, a value that is in good agreement with the 002 plane of g‐C 3 N 4 ,…”
Section: Resultssupporting
confidence: 56%
“…Compared to ultrathin GCNs, g‐CNQDs have smaller sizes, which can be useful not only for enhancing dispersibility and stability of the nanocarrier in physiological conditions, but also more suitable for cellular uptake and bioavailability performance ,. Chu et al . reported g‐CNQDs as agents for microwave induced photodynamic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In photodynamic therapy, other types of photosensitizer were investigated such as graphitic-phase carbon nitride (g-C 3 N 4 ) quantum dots (QDs). The results of live/dead staining and flow cytometry in Chu et al study showed that g-C3N4 QD-based photodynamic therapy could effectively kill cancer cells and promoted tumor cell death (Chu et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Graphitic C 3 N 4 quantum dots (g‐C 3 N 4 QDs) have received increasing attention in the fields of bioimaging, cancer therapy, ion detection, optoelectronic devices, and photocatalysis during the last decade due to their good stability, water solubility, biocompatibility, low‐toxicity, and excellent intrinsic fluorescence properties. The g‐C 3 N 4 QDs show stronger fluorescence and higher quantum yield (QY) than carbon‐based QDs, including graphene and graphene oxide QDs .…”
Section: Introductionmentioning
confidence: 99%